Cevaplar

  • Eodev Kullanıcısı
2012-12-11T17:52:53+02:00
If f ( x ) = 3x-1 and g ( x ) = 2x +3 whats f(g(2))? if f ( x ) = 3x-1 and g ( x ) = 2x +3 whats f(g(2))?


thank you explain step by step, I am really dumb right now and forgot how to do this. Its been awhile lol
I got 35 
Whats the real answer
also
this one
if f (x ) = 2x -1 what is f (x -1)?
is it -4? 4 years ago Report Abuse Additional Details show your work please

4 years ago

or could it be 2 for the second one?

4 years ago

OHHHHHHHHH i see, wow forgot all this stuff

4 years ago

0